Isolation, Identification, and Inhibition of Saponin Isolates from Pineapple (Ananas comosus L.) and Candlenut (Aleurites moluccanus L.) against Xanthine Oxidase by In Vitro Assay. Issue 1 (May 2020) - Amalia, Mimma; Alvionita, Mieke; Subandi; Susanti, Evi; Nugraheni, Dian
Abstract: The exploration of gout treatment agent based on the natural product gains high attention in recent years. Although some current drugs effectively treat gout, fewer unbeneficial effects cannot be avoided. Thus, searching for new alternatives with fewer side effects is needed. This present work was aimed at investigating the potency of saponins in pineapple ( Ananas comosus L.) and candlenut ( Aleurites moluccanus L.) extract as an inhibitor of xanthine oxidase, an enzyme that responsible for gout disease, by in vitro study. The stage of this work was divided into six stages, including (1) sample preparation, (2) extraction of saponins using 70% ethanol, (3) isolation of saponins by thin-layer chromatography, (4) phytochemical test of saponins, (5) inhibitory activity testing of saponins using in vitro analysis, and (6) determination the types of saponins by UV-Vis, FT-IR and LC-MS/MS spectroscopy. The result from the preparative TLC of pineapple extract, there were three spots with Rf value of 0.95 (pi1), 0.65 (pi2), and 0.38 (pi3), while from candlenut extract there were two saponin isolates with Rf value of 0.95 (ci1) and 0.79 (ci2). The inhibition activity of each isolate against xanthine oxidase was 103.41% (pi1), 269.73% (pi2), 84.16% (pi3), 222.90% (ci1), and 157.05% (ci2) relative to Allopurinol 100 ppm. Based on spectroscopic analysis results, isolate with the greatest inhibition activity was likely a diosgenin type (C27 H42 O3 ) of saponin.